Traditional Arab Language Teaching Adapted to English Language Teaching at MTs Nurul Huda VII - Firmansyah, Muhammad; Nur Tjendani, Endah; Ismaili, Ismaili (Linguapedia, 2024)
Sorogan is a teaching method by facing the teacher one by one by bringing the book to be studied. This sorogan method is the most difficult method of the entire education system in pesantren. Because this system requires patience, diligence, obedience, and personal discipline from students. This research aims to adapt Arabic language teaching to English and explain the successful application of the Sorogan method in Arabic. The general focus of this research is to study/examine the nature or structure of experience in human consciousness using a qualitative methodology that applies subjectivity and interpersonal skills in the exploratory research process. The results of the research can be concluded that when the researcher was explaining how to teach using the Sorogan method. Students will focus on translation only, and the teacher will focus on finding errors in the words the students read. And the teacher will explain the meaning of the material when he finds sentences that need to be explained. And sometimes the teacher will ask about the form of a word, phrase or sentence which the teacher knows he has explained.